The influence of alkyl substitution on the in vitro metabolism and mutagenicity of benzo[a]pyrene. (25th August 2022) - Wang, Danlei; Groot, Angelique; Seidel, Albrecht; Wang, Lulu; Kiachaki, Effimia; Boogaard, Peter J.; Rietjens, Ivonne M.C.M.
Abstract: In recent years concerns over consumer exposure to mineral oil aromatic hydrocarbons (MOAH), especially those containing alkylated polycyclic aromatic hydrocarbons (PAHs), have emerged. This is especially due to the fact that some PAHs are known to be genotoxic and carcinogenic upon metabolic activation. However, available toxicological data on PAHs mainly relate to non-substituted PAHs with limited data on alkyl substituted PAHs. Therefore, the aim of the present study was to characterize in more detail the effect of alkyl substitution on the metabolism and mutagenicity of benzo[ a ]pyrene (B[ a ]P), a PAH known to be genotoxic and carcinogenic. To this end, the oxidative metabolism and mutagenicity of B[ a ]P and a series of its alkyl substituted analogues were quantified using in vitro microsomal incubations and the Ames test. The results obtained reveal that upon alkylation the metabolic oxidation shifts to the aliphatic side chain at the expense of aromatic ring oxidation. The overall metabolism, including metabolism via aromatic ring oxidation resulting potentially in bioactivation, was substantially reduced with elongation of the alkyl side chain, with metabolism of B[ a ]P with an alkyl substituent of >6 C atoms being seriously hampered. In the Ames test upon metabolic activation, the methyl substitution of B[ a ]P resulted in an increase or decrease of the mutagenic potency depending on the substitution position. The relevant pathways for mutagenicity of the selected monomethyl substituted B[ a ]P may involve the formation of a 7, 8-dihydrodiol-9, 10-epoxide, a 4, 5-oxide and/or a benzylic alcohol as an oxidative side chain metabolite which subsequently may give rise to an unstable and reactive sulfate ester conjugate. It is concluded that alkylation of B[ a ]P does not systematically reduce its mutagenicity in spite of the metabolic shift from aromatic to side chain oxidation. Highlights: Methylation of B[ a ]P shifts the metabolism to alkyl oxidation. Methylation of B[ a ]P alters the mutagenic potency upon bioactivation in Ames test. Mutagenic potency of methyl-B[ a ]P depends on substitution position and tester strain. Alkylation of B[ a ]P does not systematically reduce its mutagenicity.